Effects of vegetation restoration on soil fungi community structure and assembly process in a semiarid alpine mining region - Xue, Yuanyuan; Liu, Wei; Feng, Qi; Zhu, Meng; Zhang, Jutao; Wang, Lingge; Chen, Zexia; Li, Xuejiao (Frontiers in Plant Science, 2025)
IntroductionUnderstanding responses of soil fungal community characteristics to vegetation restoration is essential for optimizing artificial restoration strategies in alpine mining ecosystems. Despite its ecological significance, current comprehension regarding the structure composition and assembly mechanisms of soil fungal communities following vegetation restoration in these fragile ecosystems remains insufficient.MethodsWe used the high-throughput sequencing and null model analysis to determine the variations and environmental drivers of soil fungal community structures and assembly processes across different restoration chronosequences (natural plant sites, unrestored sites, 2-year restoration sites, and 6-year restoration sites) in a semiarid alpine coal mining region.ResultsArtificial vegetation restoration significantly enhanced the α diversity of soil fungal communities while reducing β diversity. However, with prolonged restoration duration, we observed a significant decrease in α diversity accompanied by a corresponding increase in β diversity. Moreover, artificial restoration induced substantial modifications in soil fungal community composition. Taxonomic analysis demonstrated a distinct shift in dominant specialist species from Ascomycota in unrestored, natural plant, and 2-year restoration sites to Glomeromycota in 6-year restoration sites. Dispersal limitation and homogeneity selection were the predominant mechanism governing soil fungal community assembly, with its relative contributions varying significantly across restoration stages. In natural plant communities and unrestored sites, the structure of soil fungal community was primarily governed by dispersal limitation. The 2-year restoration sites exhibited a marked transition, with homogeneous selection emerging as the dominant assembly process, primarily influenced by soil sand content, total phosphorus (TP), total potassium (TK), and belowground biomass (BGB). This transition was accompanied by a significant reduction in the contribution of dispersal limitation.DiscussionAs restoration progressed, the importance of homogeneous selection gradually decreased, while dispersal limitation regained prominence, with community structure being predominantly regulated by soil clay content, soil moisture content (SMC), and TP. Our results underscore the critical role of soil texture and phosphorus availability in shaping soil fungal community dynamics throughout the revegetation process.